Effects of Volatiles from Clavigralla tomentosicollis Stål. (Hemiptera: Coreidae) Adults on the Host Location Behavior of the Egg Parasitoid Gryon fulviventre (Crawford) (Hymenoptera: Scelionidae). (January 2019) - Sanou, Apolline; Traoré, Fousséni; Ba, Malick Niango; Dabiré-Binso, Clémentine L; Pittendrigh, Barry R; Sanon, Antoine
The egg parasitoid Gryon fulviventre is a potential biological control agent of Clavigralla tomentosicollis, a coreid pod-sucking pest of Vigna unguiculata . The host location behavior of naive parasitoid females was studied using a four-armed olfactometer. Two strains of G. fulviventre parasitoids from Burkina Faso and Benin were exposed to odors provided by healthy and infested pods as well as C. tomentosicollis females and males. The time spent in each odor zone was recorded to determine the preference of parasitoid females. Results show that odors from healthy pods, infested pods, and pest females did not attract the parasitoid. However, a significantly attractive response of both strains of G. fulviventre was recorded in the presence of volatiles from males of C. tomentosicollis . Moreover, experiments testing G. fulviventre females' behavior when simultaneously exposed to volatiles from cowpea pods (healthy and infested) and increasing numbers of C. tomentosicollis males revealed a significantly higher attraction of parasitoid females of both strains by volatiles from ten males of C. tomentosicollis . The results suggest that the males of the insect pest emit a pheromone used as kairomone by parasitoids to locate their host. The conditions determining this attractiveness at field level and its impact on host-searching efficiency are discussed.